Resafa, Syrien: Die Arbeiten der Jahre 2012 und 2013 - Konrad, Michaela; Sack, Dorotheé; Gussone, Martin (e-Forschungsberichte des DAI, 2023)
Due to the civil war in Syria, the Resafa-project’s research has been focused on scholarly analyses of fieldwork conducted until 2011. Furthermore, studies on economic and infrastructural networks of the site could be supported by archaeometric analyses of pottery samples. The various results were presented in contributions to international journals and conferences. Since 2013, the project has been supervised by Michaela Konrad (Bamberg University).